GLP-1 Improves Adipocyte Insulin Sensitivity Following Induction of Endoplasmic Reticulum Stress - Jiang, Yaojing; Wang, Zhihong; Ma, Bo; Fan, Linling; Yi, Na; Lu, Bin; Wang, Qinghua; Liu, Rui (Frontiers in Pharmacology, 2018)
Glucagon-like peptide 1 (GLP-1) improves insulin resistance of adipose tissue in obese humans. However, the mechanism of this effect is unclear. Perturbation of endoplasmic reticulum (ER) homeostasis impairs insulin signaling. We hypothesized that GLP-1 could directly improve insulin signaling in ER-stressed adipocytes. Here, we examined the effects of GLP-1 on ER stress response in fat cells in an obese and insulin-resistant murine model. We found that GLP-1 analogue liraglutide reduced ER stress related gene expression in visceral fat cells accompanied by improved systemic insulin tolerance. Consistently, GLP-1 decreased CHOP expression and increased insulin stimulated AKT phosphorylation (p-AKT) in thapsigargin, a ER stress inducer, treated white fat cells differentiated from visceral stromal vascular fraction. We further found blocking CHOP expression increased insulin stimulated p-AKT in ER-stressed fat cells. Of note, we found mTOR signaling pathway contributed to the expression of ATF4 and subsequently the CHOP expression in ER stress response, while GLP-1 inhibited mTOR activity as exemplified by elevated autophagosome formation and increased LC3II/LC3I ratio. These findings suggest that GLP-1 directly modulates the ER stress response partially via inhibiting mTOR signaling pathway, leading to increased insulin sensitivity in adipocytes.